Perceived Organizational Support as a moderating variable on influence Well-being towards Work Engagement - Astuti, Ambar Kusuma; Hardiyanto, Purnawan; Putra, Alfa Santoso Budiwidjojo (PT Inovasi Pratama Internasional, 2023)
Work engagement is one of the things that is necessary for the progress of the organization. Employees who are involved in their work will have the motivation to consistently contribute. Previous research has shown that there is a driving force needed so that employees are willing to mobilize their resources to achieve organizational goals. One of the predictors that can affect engagement is employee well-being. Employees who have experienced prosperity will be willing to return the favor by showing dedication. In addition to well-being, the existence of support from the organization has the potential to moderate work engagement. Various forms of positive support given will make employees more enthusiastic at work. Based on this, this study aims to examine the role of the variable perceived organizational support (POS) in strengthening the effect of well-being on work engagement. Social exchange theory is used to help understand the interrelationships between variables. The research was conducted on employees in the food industry in Indonesia. Variable indicators adapted from previous studies. All the indicators used are reflexive. The primary data that has been obtained is tested using the SmartPLS software. The results of the study show that well-being and POS affect work engagement. The effect of well-being on work engagement is moderated by POS.